Fraud Pentagon Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Yang Menerapkan Asean Corporate Governance Scorecard - Julia Vivi Maulidah; Sarwenda Biduri; Nurasik Nurasik; Wiwit Hariyanto (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
The purpose of the study is represented by a repeat of CEOs' pictures against financial targets, opportunities from ineffective oversight, rationalization of auditors, revenue-driven skills, and balance sheet reporting of companies implementing ASEAN groups. It is to examine the effects of arrogance. Administrative performance map for the 2018-2020 season. This study uses a quantitative approach. The sample used consisted of his 15 companies that had implemented the ASEAN Corporate Governance Scorecard in the period 2018-2020. The data used in this study are secondary data obtained from company financial statements and annual reports obtained from the investment gallery of Muang Madhya University, Sidoarjo. The data analysis method is multiple regression analysis using the SPSS v26 program. The results of this study show that (1) Financial targets do not influence financial fraud; (2) Ineffective oversight influences financial fraud; (3) Auditor rotation does partially indicates that it does not affect reporting. Report; (4) Direction change impacts fraudulent financial reporting; and (5) Number of repeated CEO impacts fraudulent financial reporting